Neural correlates of reward processing: Functional dissociation of two components within the ventral striatum. Issue 2 (9th December 2020) - Grill, Filip; Nyberg, Lars; Rieckmann, Anna
Abstract: Introduction: Rewarding and punishing stimuli elicit BOLD responses in the affective division of the striatum. The responses typically traverse from the affective to the associative division of the striatum, suggesting an involvement of associative processes during the modulation of stimuli valance. In this study, we hypothesized that fMRI responses to rewards versus punishments in a guessing card game can be disassociated into two functional component processes that reflect the convergence of limbic and associative functional networks in the ventral striatum. Methods: We used fMRI data of 175 (92 female) subjects from the human connectome project´s gambling task, working memory task, and resting‐state scans. A reward > punish contrast identified a ventral striatum cluster from which voxelwise GLM parameter estimates were entered into a k‐means clustering algorithm. The k‐means analysis supported separating the cluster into two spatially distinct components. These components were used as seeds to investigate their functional connectivity profile. GLM parameter estimates were extracted and compared from the task contrasts reward > punish and 2‐back > 0‐back from two ROIs in the ventral striatum and one ROI in hippocampus. Results: The analyses converged to show that a superior striatal component, coupled with the ventral attention and frontal control networks, was responsive to both a modulation of cognitive control in working memory and to rewards, whereas the most inferior part of the ventral striatum, coupled with the limbic and default mode networks including the hippocampus, was selectively responsive to rewards. Conclusion: We show that the fMRI response to rewards in the ventral striatum reflects a mixture of component processes of reward. An inferior ventral striatal component and hippocampus are part of an intrinsically coupled network that responds to reward‐based processing during gambling. The more superior ventral striatal component is intrinsically coupled to networks involved with executive functioning and responded to both reward and cognitive control demands. Abstract : Using k‐means clustering, the striatal fMRI response to rewards can be separated into functional components.